EXCAVATIONS OF DERBENT SETTLEMENT IN 2014 - Gadziev, M S; Budajciev, A L; Abdulaev, A M; Sausev, K B (History, Archeology and Ethnography of the Caucasus, 2016)
The article is dedicated to the results of excavations of Derbent settlement which existed before construction of the Derbent defensive complex at the end of 560-s. The cultural layers and the construction remains of the 3-rd – 6-th centuries AD, the medieval Muslim burials which have been dug in the cultural layer were open on the area XXV. The received materials characterize culture and life of the ancient Derbent settlement which is identified with the city-fortress of Chor/Chol known for ancient Armenian, Georgian, Syrian, Early Byzantine and Arab authors and which was the important administrative, strategic and religious center of East Caucasus.
Keywords: Derbent; Chor; settlement; Late Antiquity; Early Medieval times